Friction and wear of a piston ring/cylinder liner at the top dead centre: Experimental study and modelling. (February 2017) - Zabala, B.; Igartua, A.; Fernández, X.; Priestner, C.; Ofner, H.; Knaus, O.; Abramczuk, M.; Tribotte, P.; Girot, F.; Roman, E.; Nevshupa, R.
Abstract: Wear assessment of critical components subjected to relative sliding is a key factor for the development of advanced materials and surface treatments in automotive industry. Simulation of wear process of the engine components is considered as a good alternative for experimental testing which is costly and time-consuming, but it requires a reliable experimental data for model fine-tuning. Therefore, friction and wear of cylinder liner against a piston ring were experimentally studied in simulated laboratory tests. The parameters which were controlled in these tests included oil type, lubrication starvation, surface finishing and surface coatings. The obtained experimental data were fed into a specific simulation model (AVL Excite-Power Unit). Comparison of experimental and simulated results yielded the error below 5%. Highlights: Coated piston rings with various coatings against cylinder liner with two different honing processes have been tested. DLC coatings yielded the lowest friction and wear rate among the studied coatings. The influence of lubricant in friction and wear reduction has been explained through XPS tests. A model of the pin-on-disc reciprocating tests was developed in AVL Excite software for engines design. The evolution of the friction coefficient, the wear amount and the regime modeled were validated.